Przeprowadź redukcję wyrazów podobnych.

a) 7a+3b+4c+5a-2b-8c
b) 2a-4b-5c-6a-3b+2c
c) 4a-2b+3-3a+6b-9
d) -4a+5b-7-2a-3b+3
e) 3x+5y-4x+6y-7x-9y
f) -5x+2y-4x+5y+6x-3y
g) -2x+3y+3-2y-3x-4+y-4x+2
h) x-2y-4-2x-5+y-3+2x-6y

Proszę pomóżcie mi
pliiissss

3

Odpowiedzi

2010-03-16T16:05:42+01:00
A) 7a+3b+4c+5a-2b-8c=12a-5b+12c
b) 2a-4b-5c-6a-3b+2c=8a-7b-8c
c) 4a-2b+3-3a+6b-9=7a-7b+3c
d) -4a+5b-7-2a-3b+3=3a-14b
e) 3x+5y-4x+6y-7x-9y=21x+21y
f) -5x+2y-4x+5y+6x-3y=12x+23y
g) -2x+3y+3-2y-3x-4+y-4x+2=5x-17y
h) x-2y-4-2x-5+y-3+2x-6y=3x-5y
Najlepsza Odpowiedź!
2010-03-16T16:08:35+01:00
A) 7a+3b+4c+5a-2b-8c=12a+b-4c
b) 2a-4b-5c-6a-3b+2c=-4a-7b-3c
c) 4a-2b+3-3a+6b-9=a+4b-6
d) -4a+5b-7-2a-3b+3=-6a+2b-4
e) 3x+5y-4x+6y-7x-9y=-8x+2y
f) -5x+2y-4x+5y+6x-3y=-3x+4y
g) -2x+3y+3-2y-3x-4+y-4x+2=-9x+2y+1
h) x-2y-4-2x-5+y-3+2x-6y=x-7y-12
2010-03-16T16:11:27+01:00
A) 7a+3b+4c+5a-2b-8c= 12a+ b-4c
b) 2a-4b-5c-6a-3b+2c= -4a-7b-3c
c) 4a-2b+3-3a+6b-9= a+ 4b-6
d) -4a+5b-7-2a-3b+3= -6a+2b-4
e) 3x+5y-4x+6y-7x-9y= -8x+2y
f) -5x+2y-4x+5y+6x-3y= -3x+4y
g) -2x+3y+3-2y-3x-4+y-4x+2= -9x+2y+1
h) x-2y-4-2x-5+y-3+2x-6y= x-7y-12